A novel duplication of PRMD13 causes North Carolina macular dystrophy: overexpression of PRDM13 orthologue in drosophila eye reproduces the human phenotype. - Manes, G.; Joly, W.; Guignard, T.; Smirnov, V.; Berthemy, S.; Bocquet, B.; Audo, I.; Zeitz, C.; Sahel, J.; Cazevieille, C.; Sénéchal, A.; Deleuze, J.F.; et al. (Human Molecular Genetics, 2017)
In this study, we report a novel duplication causing North Carolina macular dystrophy (NCMD) identified applying whole genome sequencing performed on eight affected members of two presumed unrelated families mapping to the MCDR1 locus. In our families, the NCMD phenotype was associated with a 98.4?kb tandem duplication encompassing the entire CCNC and PRDM13 genes and a common DNase 1 hypersensitivity site. To study the impact of PRDM13 or CCNC dysregulation, we used the Drosophila eye development as a model. Knock-down and overexpression of CycC and CG13296, Drosophila orthologues of CCNC and PRDM13, respectively, were induced separately during eye development. In flies, eye development was not affected, while knocking down either CycC or CG13296 mutant models. Overexpression of CycC also had no effect. Strikingly, overexpression of CG13296 in Drosophila leads to a severe loss of the imaginal eye-antennal disc. This study demonstrated for the first time in an animal model that overexpression of PRDM13 alone causes a severe abnormal retinal development. It is noteworthy that mutations associated with this autosomal dominant foveal developmental disorder are frequently duplications always including an entire copy of PRDM13, or variants in one DNase 1 hypersensitivity site at this locus.